Biomass production of Scenedesmus sp. and removal of nitrogen and phosphorus in domestic wastewater (2017)
(Eng) Domestic wastewater (DW) has been used as a substrate for both microalgae biomass production and nutrient removal. Biological treatment with photosynthetic microalgae provides aeration, reducing operating costs and the risk of volatilization of contaminants. It also provides oxygen to the bacteria for degradation of organic compounds. In this study, a microalga was isolated and identified as Scenedesmus sp. An experimental trial was performed using synthetic wastewater with different concentrations of N (40, 90 and 150 mg/L) and P (4, 15 and 50 mg/L). Each assay was inoculated with 1x106 cells/ml under 16h of continuous light at 50-µmol m-2 s-1 at and 120 rpm for 7 days. Samples were taken at 0, 3, 5 and 7 days to determine the growth of microalgae and the concentration of nitrates, ammonium and phosphorus. The same treatment was carried out using real DW. Synthetic water of low and medium concentration had higher removal percentages. These were between 50 and 60 for nitrogen and 40 and 70 for phosphorus, with a maximum growth of 1x107 cells /ml. For real DW, the removal was 65% for phosphorus and 80% for nitrogen. These results suggest Scenedesmus sp could be used to treat DW, enhancing nutrient removal and obtaining biomass for other purposes.